Influence of age and sex on drop jump landing strategies in elite youth soccer players - Lucarno, S.; Zago, M.; Rossi, E.; Muratore, S.; Baroncini, G.; Alberti, G.; Gualtieri, D. (International Journal of Sports Science & Coaching, 2021)
The vertical drop jump (VDJ) test evaluates frontal-plane knee control in a controlled environment. Age- and sex-related changes in landing and bouncing mechanisms in youth soccer players are still under investigated. This study characterizes knee biomechanics in a large cohort of élite academy players, stratified by sex and age group. A sample of 189 young soccer players (132 male U10-U12 and U14-U17, 57 females U10-U14) from the Academy of a professional "Serie A" Italian club were tested. Motion capture technology was used to obtain sagittal and frontal plane knee angles, as well as VDJ landing asymmetry and peak vertical ground reaction forces at push-off. Landing kinetics and kinematics changed as a function of age and sex in youth élite soccer players: (i) males and females showed different landing load asymmetry between dominant and non-dominant leg, peak push-off force and knee flexion even before puberty, (ii) landing asymmetry tended to reduce in older players and (iii) knee varus increased in males after adolescence. In conclusion, besides its role in injury prevention, the VDJ can help in monitoring players` growth and development, and this process should start at an early age. This data collection could be used as a tool for further screening test to highlight anomalous landing behaviour.